2012
DOI: 10.1002/ett.1544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carrier frequency offset and symbol timing offset on the performance of FMT over time‐frequency selective channels

Abstract: This paper presents the effects of carrier frequency offset (CFO) and symbol timing offset (STO) in filtered multitone (FMT) systems over time and frequency selective multipath fading channels. The analysis is based on an FMT system using a square-root raised cosine pulse. The performance of FMT systems in the presence of CFO and STO over different fading channels are derived and compared with that of orthogonal frequency division multiplexing systems. The offsets degrade the performance of the FMT systems bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In FBMC that recently attracts attention for using in the future communication systems [5]- [8], the prototype filters with well-localised pulse shapes in time and frequency are used instead of rectangular window. The authors in [3], [9] and [10] have shown that the FBMC systems produce much better performance than OFDM system against time and frequency variations because of using well-localised pulse shaping. For example, in acoustic underwater channel that is very time variable, FBMC can be used, effectively [11].…”
Section: Introductionmentioning
confidence: 99%
“…In FBMC that recently attracts attention for using in the future communication systems [5]- [8], the prototype filters with well-localised pulse shapes in time and frequency are used instead of rectangular window. The authors in [3], [9] and [10] have shown that the FBMC systems produce much better performance than OFDM system against time and frequency variations because of using well-localised pulse shaping. For example, in acoustic underwater channel that is very time variable, FBMC can be used, effectively [11].…”
Section: Introductionmentioning
confidence: 99%